2018
DOI: 10.1186/s12933-018-0735-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between epicardial adipose tissue, high-sensitivity C-reactive protein and myocardial dysfunction in middle-aged men with suspected metabolic syndrome

Abstract: BackgroundAs body fat composition and metabolism differ between men and women, we evaluated sex-related differences in the association among epicardial adipose tissue (EAT), secretome profile, and myocardial function of subjects with suspected metabolic syndrome.MethodsWe evaluated 277 participants (men, n = 140; 56.1 ± 4.7 years) who underwent conventional echocardiography and two-dimensional speckle tracking from the Seoul Metabolic Syndrome cohort. EAT was measured from the right ventricular free wall perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 53 publications
2
38
3
1
Order By: Relevance
“…Iacobellis et al [21] reported a similar reduction in epicardial fat volume after treatment with liraglutide (up to 1.8 mg/day for 3 and 6 months) and it was recently reported that epicardial adipose tissue expresses the GLP-1 receptor [31]. This is of clinical importance, since it was recently shown that inflammatory activity of epicardial adipose tissue volume might induce myocardial remodelling and dysfunction [32]. In the current study, a reduction of either epicardial or…”
Section: Discussionsupporting
confidence: 76%
“…Iacobellis et al [21] reported a similar reduction in epicardial fat volume after treatment with liraglutide (up to 1.8 mg/day for 3 and 6 months) and it was recently reported that epicardial adipose tissue expresses the GLP-1 receptor [31]. This is of clinical importance, since it was recently shown that inflammatory activity of epicardial adipose tissue volume might induce myocardial remodelling and dysfunction [32]. In the current study, a reduction of either epicardial or…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have suggested that measurements of EFT are a substitute for visceral fat [8,9] EFT can secrete inflammatory factors, such as TNF-alpha, IL-6, adipocytokines, and leptin, via paracrine or endocrine activities [9,10] to locally regulate the myocardium and coronary artery function and regulate lipid and energy homeostasis in vivo. EFT has the ability to release and uptake free fatty acids and to affect low glucose utilization, which plays an important role in metabolic syndrome and coronary artery disease [11][12][13][14][15][16]. EFT can be measured by echocardiography, cardiac magnetic resonance imaging, and computed tomography (CT) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The present study results, generated from a large sample, also strongly support the regional effects of PAT on LV systolic function, independent of general obesity measures and gender (data not shown). However, one study found that the association of EAT with impaired LV systolic function assessed by strain and TDI techniques was observed only in men [28].…”
Section: Discussionmentioning
confidence: 99%